Immunity to Respiratory Infection Is Reinforced Through Early Proliferation of Lymphoid TRM Cells and Prompt Arrival of Effector CD8 T Cells in the Lungs - Suarez-Ramirez, Jenny E.; Chandiran, Karthik; Brocke, Stefan; Cauley, Linda S. (Frontiers in Immunology, 2019)
Cross-protection between serologically distinct strains of influenza A virus (IAV) is mediated by memory CD8 T cells that recognize epitopes from conserved viral proteins. Early viral control begins with activation of tissue-resident memory CD8 T cells (TRM) cells at the site of viral replication. These CD8 T cells do not act in isolation, as protection against disseminated infection is reinforced by multiple waves of effector cells (TEFF) that enter the lungs with different kinetics. To define how a protective CTL response evolves, we compared the functional properties of antiviral CD8 T cells in the respiratory tract and local lymphoid tissues. When analyzed 30dpi, large numbers of antiviral CD8 T cells in the lungs and mediastinal lymph nodes (MLNs) expressed canonical markers of tissue-resident memory CD8 T cells (TRM) cells (CD69 and/or CD103). The check point inhibitor PD-1 was also highly expressed on NP-specific CD8 T cells in the lungs, while the ratios of CD8 T cells expressing CD69 and CD103 varied according to antigen specificity. We next used in vitro experiments to identify conditions that induce a canonical TRM phenotype and found that that naïve and newly activated CD8 T cells maintain CD103 expression during culture with transforming growth factor-beta (TGF), while central memory CD8 T cells (TCM) do not express CD103 under similar conditions. In vivo experiments showed that the distribution of antiviral CTLs in the MLN changed when immune mice were treated with reagents that block interactions with PD-L1. Importantly, the lymphoid TRM cells were poised for early proliferation upon reinfection with a different strain of IAV and defenses in the lungs were augmented by a transient increase in numbers of TEFF cells at the site of infection. As the interval between infections increased, lymphoid TRM cells were replaced with TCM cells which proliferated with delayed kinetics and contributed to an exaggerated inflammatory response in the lungs.